OX40 Agonists and Combination Immunotherapy: Putting the Pedal to the Metal - Linch, Stefanie N.; McNamara, Michael J.; Redmond, William L. (Frontiers in Oncology, 2015)
Recent studies have highlighted the therapeutic efficacy of immunotherapy, a class of cancer treatments that utilize the patient’s own immune system to destroy cancerous cells. Within a tumor the presence of a family of negative regulatory molecules, collectively known as “checkpoint inhibitors”, can inhibit T cell function to suppress anti-tumor immunity. Checkpoint inhibitors, such as CTLA-4 and PD-1, attenuate T cell proliferation and cytokine production. Targeted blockade of CTLA-4 or PD-1 with antagonist monoclonal antibodies (mAb) releases the “brakes” on T cells to boost anti-tumor immunity. Generating optimal “killer” CD8 T cell responses also requires T cell receptor activation plus co-stimulation, which can be provided through ligation of tumor necrosis factor receptor family members, including OX40 (CD134) and 4-1BB (CD137). OX40 is of particular interest as treatment with an activating (agonist) anti-OX40 mAb augments T cell differentiation and cytolytic function leading to enhanced anti-tumor immunity against a variety of tumors. When used as single agents, these drugs can induce potent clinical and immunologic responses in patients with metastatic disease. However, each of these agents only benefits a subset of patients, highlighting the critical need for more effective combinatorial therapeutic strategies. In this review, we will discuss our current understanding of the cellular and molecular mechanisms by which OX40 agonists synergize with checkpoint inhibitor blockade to augment T cell-mediated anti-tumor immunity and the potential opportunities for clinical translation of combinatorial immunotherapeutic strategies.